2021
DOI: 10.1186/s13244-021-01098-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in diagnosis of indeterminate breast (BIRADS 3 & 4A) in a general population

Abstract: Objective Currently, mammography and ultrasonography are the most used imaging techniques for breast cancer screening. However, these examinations report many indeterminate studies with a low probability of being malignant, i.e., BIRADS 3 and 4A. This prospective study aims to evaluate the value of breast magnetic resonance imaging (MRI) to clarify the BIRADS categorization of indeterminate mammography or ultrasonography studies. Methods MRI studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In their cohort malignancy was excluded in 82% as only three additional carcinomas (3%) were diagnosed. 6 There were 149 BI-RADS 3 findings in our patient cohort. Although they showed characteristic contrast enhancement for fibroadenomas, all patients were recalled for a short-term follow-up examination, according to the BI-RADS guidelines.…”
Section: Discussionmentioning
confidence: 84%
“…In their cohort malignancy was excluded in 82% as only three additional carcinomas (3%) were diagnosed. 6 There were 149 BI-RADS 3 findings in our patient cohort. Although they showed characteristic contrast enhancement for fibroadenomas, all patients were recalled for a short-term follow-up examination, according to the BI-RADS guidelines.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors have also suggested MRI as a sensitive problem solving modality in indeterminate breast lesions. 13 …”
Section: Discussionmentioning
confidence: 99%